Macroeconomy of Riau Province and Government Policies Overcoming the Impact of Covid-19 Pandemic - Mardiana Mardiana; Eriyati Eriyati; Ritayani Iyan; Toti Indrawati; Dahlan Tampubolon (Universitas Kadiri, 2022)
This article aims to analyze the impact of Covid 19 on the macroeconomy of Riau Province, including economic growth, investment, public consumption, and inflation in Riau Province and Riau Province government policies to overcome them. This study takes data related to macroeconomics in Riau, uses secondary data. Covid 19 caused a decrease in economic growth compared to the period before Covid 19. Covid 19 did not have a too significant impact on investment in Riau Province. The condition even shows an increase in investment compared to the previous year. Covid 19 caused a significant decrease in public consumption in Riau Province. Covid 19 causes inflationary instability in Riau. The Riau Provincial government's policy in controlling the impact of Covid 19 on the macroeconomic sector is through refocusing as the Covid recovery budget in Riau and supporting the realization of the National Economic Recovery fund budgeted by the Central Government. The government's policy is to ensure the implementation of infrastructure development (toll roads and provincial roads) to support distribution, agricultural incentives, labor-intensive projects, SME assistance, Pre-Employment Cards, and other policies aimed at ensuring economic stability in Riau Province.